The transit of Venus - Hazzard, Shirley, 1931-2016 (Penguin Books, 1990)
This book tells the story of two orphan sisters, Caroline and Grace Bell, as they leave Australia to start a new life in post-war England. What happens to these young women--seduction and abandonment, marriage and widowhood, love and betrayal--becomes as moving and wonderful and yet as predestined as the transits of the planets themselves. Gorgeously written and intricately constructed, Hazzard's novel is a story of place: Sydney, London, New York, Stockholm; of time: from the fifties to the eighties; and above all, of women and men in their passage through the displacements and absurdities of modern life.